2014
DOI: 10.12944/crnfsj.2.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parental E ducation and Illness with Obesity and Blood Pressure in 13-16 Year Old Girls

Abstract: The aim of the current study was to estimate the prevalence of hypertension and obesity and its associations with parental (or grandparental) history of illness and parental education. A cross-sectional study was conducted among 299 girls aged 13-16 years from Mumbai city, India. Anthropometry (weight, height, waist (WC) and hip circumference, mid-upper arm circumference) and blood pressure (BP) was measured. History of chronic illness in parents and grandparents was recorded. Parental education was also recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Of the two studies strictly from LMICs, one reported a positive association although the results from the other study were inconclusive. 24,33 The only single study from the Africa region reported a positive and significant association 33 ; and 78% of studies from the American region reported positive associations between GP-GC overweight/obesity. In comparison, 67% of studies from the European region reported a positive association.…”
Section: Association Of Gp-gc Overweight/obesity Statusmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the two studies strictly from LMICs, one reported a positive association although the results from the other study were inconclusive. 24,33 The only single study from the Africa region reported a positive and significant association 33 ; and 78% of studies from the American region reported positive associations between GP-GC overweight/obesity. In comparison, 67% of studies from the European region reported a positive association.…”
Section: Association Of Gp-gc Overweight/obesity Statusmentioning
confidence: 99%
“…Table 1 provides the main characteristics and findings of the studies included in this study. 2,3,5,6,[22][23][24][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations